Adaptive Backstepping Sliding Mode Control of Vehicle-Mounted Parallel Stabilized Platform. Issue 1 (13th October 2022) - Shenli, Wu; Ling, Liu; Xiaoming, Liang; Zimeng, Yao
Abstract: This paper researches an accurate and cooperative stability control method for the vehicle-mounted parallel stabilized platform to isolate the external random interference caused by rugged terrains. An adaptive backstepping sliding mode controller is designed by combining the adaptive method and backstepping design method. The position and pose of the platform are calculated in real time as feedback quantity and a closed-loop controller overall pose is designed. Simulation and experimental results show that the vehicle-mounted parallel stabilized platform can quickly and accurately adjust the pose of the upper platform to keep horizontal when the vehicle runs on rugged terrains.